Conversion Of Sign Language into Text and Speech Using CNN - Belekar Monika; Mungase Amruta; Pise Anjali; Prof. Dangat P. D.; Dr. Divekar S. N. (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
This research paper presents a comprehensive study on the design and implementation of a sign language to text conversion system powered by Convolutional Neural Networks (CNNs). Our work addresses the critical communication barriers faced by the deaf and hard-of-hearing communities by developing an automated framework that accurately recognizes sign language gestures from image and video inputs and converts them into corresponding textual output. The system leverages state-of-the-art deep learning techniques alongside robust image processing algorithms, ensuring real-time performance and high recognition accuracy. By integrating advanced feature extraction methods, efficient data pre-processing, and sophisticated model architectures, our approach demonstrates promising potential for practical applications in assistive technologies, education, and healthcare.